The Swing Theory of Islam: A Study of Ernest Gellner Epistemology - Supriyanto Supriyanto (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
Theory is the highest form of knowledge. As for the person who succeeds in giving birth to a theory, he can be said to be someone who really deserves ‘appreciation’. Gellner as a sociologist managed to read the social reality of Islam by giving birth to the pendulum swing theory in Islam - A Pendulum Swing Theory of Islam. This article tries to explain Ernest Gellner’s theory. From studies conducted show that: 1) His theory was born from his interest in Islam, for him Islam has a structure and character that is unique compared to religion outside, 2) The ability of Islam to respond to change without losing ‘identity’ makes the social response of Muslims in a level that ‘established.’ This second point, for Gellner, is the key to why Muslims’ social reality movements tend to ‘flux and reflux of religion’ as well as the Pendulum swing.